REOVIRUS ASSOCIATED MENINGOENCEPHALOMYELITIS IN BABOONS - Kumar, S. (2013)
Baboon orthoreovirus (BRV) is associated with meningoencephalomyelitis (MEM) among captive baboons. Sporadic cases of suspected BRV induced MEM have been observed at Southwest National Primate Research Center for the past 20 years, but could not be confirmed due to lack of diagnostic assays. An immunohistochemistry (IHC) based assay using antibody against BRV Fusion Associated Small Transmembrane protein p15, and a conventional PCR (PCR) based assay using primers specific for BRV were developed to detect BRV in archived tissues. Sixty-eight cases of suspected BRV induced MEM from 1989 to 2010 were tested for BRV, Alphavirus, and Flavivirus by immunohistochemistry. Fifty-nine out of 68 cases (87%) were positive for BRV by immunohistochemistry; one tested positive for Flavivirus (but was negative for West Nile virus and St Louis encephalitis virus by real-time PCR (qRT-PCR), and one virus isolation (VI) positive control tested negative for BRV. Sixteen cases (nine BRV negative and seven BRV positive cases, by immunohistochemistry), along with VI positive and negative controls were tested by PCR for BRV. Three (out of nine) IHC-negative cases tested positive, and three (out of seven) IHC-positive cases tested negative by PCR for BRV. Both immunohistochemistry and PCR assays tested one VI positive control as negative (sensitivity: 75 %). This study shows that the majority of cases of viral MEM among baboons at SNPRC are associated with BRV infection and the BRV should be considered as a differential for non-suppurative MEM in baboons.